Dynamics and determinants of human plasma bile acid profiles during dietary challenges - Fiamoncini, Jarlei; Rist, Manuela J.; Frommherz, Lara; Giesbertz, Pieter; Pfrang, Birgit; Kremer, Werner; Huber, Fritz; Kastenmüller, Gabi; Skurk, Thomas; Hauner, Hans; Suhre, Karsten; Daniel, Hannelore; et al. (Frontiers in Nutrition, 2022)
Bile acids (BA) have in recent years received high interest by their pleiotropic biological activity and the presence of plasma membrane-bound and nuclear receptors. Moreover, BA in blood have been identified by metabolite screening approaches as biomarkers that associate with various diseases and even with a human longevity phenotype. With the growing interest in the microbiota contribution to the health-disease trajectory, BA that undergo deconjugation and other modifications by bacteria in the large intestine have become a prime target as a microbiome diversity modifier. We here profiled BA by a quantitative and a semiquantitative approach in 15 healthy and phenotypically very similar young individuals over a 36-hour fasting period and an oral glucose tolerance test (OGTT) as well as an oral lipid tolerance test (OLTT). We demonstrate a remarkable heterogeneity of the responses and describe the different dynamics of the plasma changes that originate likely from different routes by which BA enter the peripheral blood and that may represent a direct secretion from liver into blood and a route that reaches the blood as a spill-over after passing from gallbladder through the intestine and portal system. We discuss the contribution that individual transport processes involved in passage of BA could be critical determinants in the kinetics of plasma appearance and the overall phenotypic variability found.